Some Inequalities for Bounding Toader Mean - Wen-Hui Li; Miao-Miao Zheng (Journal of Function Spaces and Applications)
By finding linear relations among differences between two special means, the authors establish some inequalities for bounding Toader mean in terms of the arithmetic, harmonic, centroidal, and contraharmonic means.